OSH 21ST CENTURY SKILLS IN A VUCA ENVIRONMENT - Abdul Hamid, Suhaila; Liza Meor Gheda, Mariatul; Fairuz Buang, Nurul; Fahzan Salleh, Khairul; Hazry Yusof, Mohd (Journal of Research and Innovation In Open and Distance Learning, 2024)
Today, businesses are operating in a VUCA environment. In the VUCA environment, Occupational Safety and Health (OSH) skills are essential for a business’s viability and sustainability since they safeguard personnel, ensure legal compliance and standards conformance, reduce operational costs, foster productivity, elevate reputation, and exhibit social responsibility. In a VUCA environment, the risk management process acts as a pillar for business viability and sustainability. With effective risk management, businesses can use it to proactively detect and reduce risks, improve adaptation and resilience, guarantee business continuity, make better decisions, and instill confidence among stakeholders. Businesses may negotiate uncertainty, grasp opportunities, and put themselves in a position for long-term success by managing risks properly. Effective risk assessors are essential to the success of risk management because they provide accurate and trustworthy assessments of potential risks. Hence, through this study, it investigates the criticality of OSH risk assessor skills in functioning in the VUCA environment; and identifies the pedagogical preferences for effective risk assessor program. A quantitative research approach is employed for this study, utilising a three (3) parts survey comprising 25 items. The study involved fifty (50) OSH practitioners as the respondents. The Relative Importance Index (RII) results for OSH risk assessor skills in a VUCA environment, assessed on a ten-point Likert scale, are as follows: applied knowledge of the subject matter (0.88), communication skills (0.87); attention to detail (0.87); risk control techniques (0.87); ethical consideration (0.87); risk assessment methodologies (0.86); analytical thinking (0.85); critical thinking (0.85); data analysis (0.84) and adaptability (0.84). Next, respondents conveyed their preferences regarding pedagogical approaches using a ten-point Likert scale. The Relative Importance Index (RII) scores for these approaches are as follows: problem-based learning (0.83); authentic assessment (0.82); inquiry-based learning (0.81); collaborative learning (0.81); technology integration (0.81); experiential learning (0.81); cultivating creativity and innovation (0.81); project-based learning (0.80); multidisciplinary and interdisciplinary approaches (0.80) and metacognitive strategies (0.79).This study contributes to the design of the OSH risk assessor programme for assisting industries in operating in the VUCA environment by helping them to understand the vision, develop situational awareness, make complex situations clear, and generate hypotheses to address potential risks, all of which lead to more informed decision-making, increased resilience, and efficient resource use.